2011
DOI: 10.1097/acm.0b013e318209897f
|View full text |Cite
|
Sign up to set email alerts
|

Humanism at Heart: Preserving Empathy in Third-Year Medical Students

Abstract: Maintaining empathy during the third year of medical school is possible through educational intervention. A curriculum that includes safe, protected time for third-year students to discuss their reactions to patient care situations during clerkships may have contributed to the preservation of empathy. Programs designed to validate humanism in medicine (such as the GHHS) may reverse the decline in empathy as measured by the JSPE-MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
12

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(120 citation statements)
references
References 17 publications
6
97
0
12
Order By: Relevance
“…While a few studies failed to demonstrate higher empathy scores among female students, reportedly due to sampling bias (Paro et al, 2012, Rahimi-Madiseh et al, 2010, Roh et al, Di Lillo et al, 2009, our findings are consistent with the results of a number of studies which suggest that gender differences, in favour of women, exist concerning empathy. (Austin et al, 2007, Hojat et al, 2003, Hojat et al, 2002a, Hojat et al, 2002b, Hojat et al, 2002c, Hojat et al, 2001, Kataoka et al, 2009, Rosenthal et al, 2011 Significant differences were found not only in the total JSPE score but also in eleven out of the twenty individual components of the scale. The largest gender difference was observed in the item related to reading interest; "I do not enjoy reading non-medical literature or the arts" (where, Z=4.871, p = .000), which coincides with the findings of Kataoka et al (Kataoka, et al, 2009) Empathy encompasses cognitive and affective/emotional dimensions.…”
Section: Empathy and Gendermentioning
confidence: 99%
“…While a few studies failed to demonstrate higher empathy scores among female students, reportedly due to sampling bias (Paro et al, 2012, Rahimi-Madiseh et al, 2010, Roh et al, Di Lillo et al, 2009, our findings are consistent with the results of a number of studies which suggest that gender differences, in favour of women, exist concerning empathy. (Austin et al, 2007, Hojat et al, 2003, Hojat et al, 2002a, Hojat et al, 2002b, Hojat et al, 2002c, Hojat et al, 2001, Kataoka et al, 2009, Rosenthal et al, 2011 Significant differences were found not only in the total JSPE score but also in eleven out of the twenty individual components of the scale. The largest gender difference was observed in the item related to reading interest; "I do not enjoy reading non-medical literature or the arts" (where, Z=4.871, p = .000), which coincides with the findings of Kataoka et al (Kataoka, et al, 2009) Empathy encompasses cognitive and affective/emotional dimensions.…”
Section: Empathy and Gendermentioning
confidence: 99%
“…We believe that our curricula, especially after the Bologna changes with the implementation of early patient contact into medical teaching (13), stimulate development of humanistic values in medical students and positively influence students' empathy. In a systematic review of studies, especially those with longitudinal data, it was found that the empathy decline during the medical study and residency compromised striving toward professionalism and may threaten health care quality (33), but there were also other reports claiming that empathy can be preserved or increased through the educational process at the medical school (11,19,26,34). An important question is also whether the self-reported empathy assessed by JSE-S is related to empathic behaviour of students and later on also to the behaviour of residents and physicians in practice (30,35).…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Curricula that include time dedicated to discuss students' reactions to patients' care and enable participation in service activities are believed to enhance the level of students' empathy (11,32).…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…These are, effectively, "train the trainers" programs. Physician-mentors should attend faculty development programs specifically aimed at equipping them with strategies to reduce learner moral distress, including open-communication strategies, facilitation skills for learners to debrief about "difficult" patients [54], the use of narrative ethics for self-reflection [55], an enhanced ethics curriculum [56], and peer-support programs [57]. Such initiatives also allow mentors to identify their own current or past experiences of moral distress, which can enable greater empathy and better communication with students.…”
Section: Medical Education Initiativesmentioning
confidence: 99%